Meningkatkan Kedisiplinan Siswa Melalui Perspektif Syariah di SMK Bina Mandiri Multimedia - Novingky Ferdinand; Guruh Herman Was'an; Rizky Maulana; Nurul Oktaviani; Siti Aminah; Komarudin Komarudin (Jurnal Pengabdian Masyarakat Madani, 2022)
The goals of national education will not be achieved without discipline. Islam is a religion that teaches discipline as well as gentleness. Students in schools should carry out a disciplined attitude by obeying all the rules that apply in their school which is called student discipline. The Covid-19 pandemic has reduced the level of student discipline, especially student discipline at school. Community service activities in the form of counseling aim to improve student discipline through a sharia perspective at SMK Bina Mandiri Syariah. The method used is counseling activities and activity evaluation. The results of the extension activities found that there were main obstacles experienced by students in the application of discipline in schools, namely the adaptation process from the online teaching and learning system to the face-to-face system. The results of the evaluation of activities are known to increase the insight and commitment of students of SMK Bina Mandiri Multimedia in applying student discipline through a Sharia perspective, both inside and outside school. This community service activity is very useful for students at Bina Mandiri Multimedia Vocational School to improve student discipline through a sharia perspective.